Digital Serious Games to Promote Behavior Change in Children With Chronic Diseases: Scoping Review and Development of a Self-Management Learning Framework - Made Ary Sarasmita; Ya-Han Lee; Fan-Ying Chan; Hsiang-Yin Chen (JMIR Publications, 2024)
BackgroundDigital serious games (SGs) have rapidly become a promising strategy for entertainment-based health education; however, developing SGs for children with chronic diseases remains a challenge. ObjectiveIn this study, we attempted to provide an updated scope of understanding of the development and evaluation of SG educational tools and develop a framework for SG education development to promote self-management activities and behavior change in children with chronic diseases. MethodsThis study consists of a knowledge base and an analytical base. This study followed the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. To build the knowledge base, 5 stages of research were developed, including refining the review question (stage 1), searching for studies (stage 2), selecting relevant studies (stage 3), charting the information (stage 4), and collating the results (stage 5). Eligible studies that developed SG prototypes and evaluated SG education for children with chronic diseases were searched for in PubMed, Embase, Google Scholar, and peer-reviewed journals. In the analytical base, the context-mechanism-output approach and game taxonomy were used to analyze relevant behavioral theories and essential game elements. Game taxonomy included social features, presentation, narrative and identity, rewards and punishment, and manipulation and control. A total of 2 researchers selected the domains for the included behavioral theories and game elements. The intended SG framework was finalized by assembling SG fragments. Those SG fragments were appropriately reintegrated to visualize a new SG framework. ResultsThis scoping review summarized data from 16 randomized controlled trials that evaluated SG education for children with chronic diseases and 14 studies on SG frameworks. It showed that self-determination theory was the most commonly used behavioral theory (9/30, 30%). Game elements included feedback, visual and audio designs, characters, narratives, rewards, challenges, competitions, goals, levels, rules, and tasks. In total, 3 phases of a digital SG framework are proposed in this review: requirements (phase 1), design and development (phase 2), and evaluation (phase 3). A total of 6 steps are described: exploring SG requirements (step 1), identifying target users (step 2), designing an SG prototype (step 3), building the SG prototype (step 4), evaluating the SG prototype (step 5), and marketing and monitoring the use of the SG prototype (step 6). Safety recommendations to use digital SG-based education for children in the post-COVID-19 era were also made. ConclusionsThis review summarizes the fundamental behavioral theories and game elements of the available literature to establish a new theory-driven step-by-step framework. It can support game designers, clinicians, and educators in designing, developing, and evaluating digital, SG-based educational tools to increase self-management activities and promote behavior change in children with chronic diseases.